Gender in Slovenian Monolingual General Explanatory Dictionaries : Rod u slovenskim jednojezičnim općim objasnidbenim rječnicima - Ledinek, Nina (Array, 2021)
In this paper, we focus on gender as a grammatical and social category in Slovenian monolingual general explanatory dictionaries and explain how the category of gender influences the selection and presentation of data included in Slovenian explanatory dictionaries, as well as their structuring at macro- and microstructural levels. We focus on the analysis of the changes that have occurred in dictionary description at the beginning of the 21st century due to the growing awareness of gender-sensitive language use, and point out some of the editorial dilemmas related to the category of gender that we face in the preparation of the eSSKJ: Dictionary of the Slovenian Standard Language, Third Edition.